REKONSTRUKSI FATWA DSN-MUI PADA PENGEMBANGAN INDUSTRI PERBANKAN SYARIAH DI INDONESIA - Faizi (AN NUR: Jurnal Studi Islam, 2012)
Trend in the development of Islamic banking industry in Indonesia in the last decade experienced a very significant development both qualitatively and quantitatively. The attractive development that is to be a pride for stakeholders of Islamic banking considering that Indonesia can be said too late, not to say left behind in responding the development of sharia-based industries and businesses if compared to other Muslim countries. However, the performance of Islamic banking financial institutions in Indonesia, slowly but surely, shows tremendous growth, even in certain level, can defeat neighboring country, Malaysia, which had long been working on Sharia-based financial sector. In the context of Indonesia, the idea of producing fatwas of Islamic banking products and services is truly derived from the results of Muslim scholars and experts’ ijtihad of Sharia economics attached to formal institution called the National Sharia Council of Indonesia Ulama Committee or DSN-MUI. This institution which then has sole authority in issuing fatwas on Islamic economics and finance in Indonesia, certainly in terms of Sharia industrial development in Indonesia.